POLITICAL STABILITY VERSUS LOCAL OLIGARCHY - Nurhadi, Sandi; Fauzan, Fauzan Hidayat (Fakultas Politik Pemerintahan, 2024)
This reserach aims to analyze the impact of the extended tenure of village heads, as regulated by Law No. 3 of 2024, on village governance, particularly in terms of accountability, leadership stability, and public participation. Using the Systematic Literature Review (SLR) approach, this research synthesizes findings from various academic sources focusing on good governance practices in local government. The results reveal that longer tenure offers opportunities for sustainable development by providing continuity in leadership and reducing political disruptions. However, it also introduces significant risks, including the potential misuse of power and a decline in public participation in supervision. The findings emphasize the need for robust monitoring mechanisms and increased community involvement to balance the benefits and risks associated with extended leadership terms. This study concludes with recommendations for strengthening transparency and accountability to improve village governance and prevent corruption in the long run.